Peran Pemimpin dalam Menyelesaikan Konflik Organisasi di Marching Band Gita Bahana Teladan Sei Rampah: Penelitian - Tasya Frista Pangaribua; Lidia Angriani Br Sinag; Muhammad Hidayat; Rotua Sahat P Simanullang (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
In the world of organizations, conflict is an unavoidable phenomenon, whether it arises among internal members or involves external parties. The problems we found after conducting research on the Gita Bahana Teladan Sei Rampah Marching Band included issues related to uneven member discipline, ineffective time management during events, limited facilities and funds to support activities, and misunderstandings between members and coaches due to poor communication. Therefore, leaders have a crucial role in directing conflict resolution so as not to disrupt the stability and productivity of the organization. This research aims to describe the role of leaders in resolving conflicts within the Gita Bahana Teladan Sei Rampah Marching Band organization using leadership models and types. The research method used by the researcher is a qualitative method based on observations and experiences. The data collection technique is a questionnaire. The output of this research is to describe the attitudes of marching band leaders in resolving conflicts effectively.